Rehabilitation Problems and Solutions in Young Oncology Patients (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Young oncology patients face unique rehabilitation challenges due to the intersection of cancer treatment with critical periods of physical, emotional, and social development. This study explores the specific rehabilitation problems encountered by adolescents and young adults (AYAs) with cancer, including delayed physical recovery, disruptions in education and employment, psychosocial distress, and long-term treatment-related complications. The research highlights that conventional rehabilitation programs often fail to address the age-specific needs of young patients, resulting in gaps in continuity of care and reduced quality of life. Drawing from recent clinical studies and patient-centered interventions, the paper identifies effective solutions such as age-adapted physical therapy, integrated psycho-oncological support, fertility preservation counseling, and peer-based social reintegration programs. Multidisciplinary and personalized rehabilitation strategies are shown to improve functional outcomes and promote resilience in this vulnerable population. The study underscores the importance of tailored rehabilitation approaches and stronger care coordination to ensure that young cancer survivors achieve optimal long-term recovery and well-being.